UDP-Glucose Dehydrogenases: Identification, Expression, and Function Analyses in Upland Cotton (Gossypium hirsutum) - Jia, Tingting; Ge, Qun; Zhang, Shuya; Zhang, Zhen; Liu, Aiying; Fan, Senmiao; Jiang, Xiao; Feng, Yulong; Zhang, Lipeng; Niu, Doudou; Huang, Shen; Gong, Wankui; et al. (Frontiers in Genetics, 2021)
UDP-glucose dehydrogenase (UGD; EC1.1.1.22) is a NAD+-dependent enzyme that catalyzes the two fold oxidation of UDP-glucose (UDP-Glc) to produce UDP-glucuronic acid (UDP-GlcA) and plays an important role in plant cell wall synthesis. A total of 42 UGD genes from four Gossypium genomes including G. hirsutum, G. arboretum, G. barbadense, and G. raimondii were identified and found that the UGD gene family has conservative evolution patterns in gene structure and protein domain. The growth of fibers can be effectively promoted after adding the UDP-Glc to the medium, and the GhUGD genes expression enhanced. In addition, the transgenic Arabidopsis lines over-expressing GH_D12G1806 had longer root lengths and higher gene expression level than the wild type plants of Columbia-0. These results indicated that UGD may play important roles in cotton fiber development and has a guiding significance for dissecting fiber development mechanism.